Intensifikasi Profil Pelajar Pancasila dan Implikasinya Terhadap Ketahanan Pribadi Siswa Pada Siswa Sekolah Menengah Atas (Studi SMA N 7 Kota Jambi) - A A Musyaffa; Umil Muhsinin; Rapiko Rapiko; Dewi Hasanah; Siti Asiah; Sunarto Sunarto; Siti Ubaidah; Ilyas Ilyas; Asmawati Asmawati (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
This community service activity was motivated by the lack of optimal strengthening of character education through Pancasila student profiles for teachers in the field. The aims of this community service activity are to; 1) strengthen character and competence, 2) actively participate in planning active and sustainable learning, 3) develop skills, attitudes and knowledge, 4) solve problems in various learning situations, 5) be responsible and care about the surrounding situation and 6) respect learning so as to achieve educational goals. Based on the training that was carried out at SMA Negeri 7 Jambi City, this service activity received a positive response from the teachers who took part in this activity. This can be seen from the high enthusiasm of the teachers when participating in this training activity. The main thing that is done during the implementation of this service activity is that teachers who are training participants are asked to identify a problem related to character education through the Pancasila student profile. Then the teachers are given an understanding of the materials and problems related to strengthening character education. As feedback from this activity, the Education Coordinator and high school teachers said that they were willing to become target schools for various activities to improve the quality of education in their schools. The hope of the Jambi City Education Coordinator and the teachers at the Senior High School is that their school performance can continue to improve with the collaboration built with the Sulthan Thaha Saifuddin Jambi Islamic State University.